2015
DOI: 10.1108/jfmm-11-2014-0079
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based development of a strategy for Canadian apparel SMEs

Abstract: Purpose – The Canadian apparel industry has long been challenged by imports from low-wage countries while its exports have declined since their height in 2002. This situation was exacerbated with trade liberalisation, which started in January 2005. Data from Industry Canada and a number of studies, amongst which those of the Apparel Human Resources Council (AHRC), showing the adverse effects of trade liberalisation since the phasing out of the multi-fibre agreement in 2005, the lack of competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…(4) The survey instrument was also provided to the students as an add-on to their normal project. This type of face-to-face survey method has been used in other published research (Lim et al, 2011;Campaniaris et al, 2015). This type of integrated method is an outgrowth of the Key Informant Survey.…”
mentioning
confidence: 99%
“…(4) The survey instrument was also provided to the students as an add-on to their normal project. This type of face-to-face survey method has been used in other published research (Lim et al, 2011;Campaniaris et al, 2015). This type of integrated method is an outgrowth of the Key Informant Survey.…”
mentioning
confidence: 99%
“…Surrounding the campus is a mix of housing, live-work studios, a hotel, supporting retail and commercial firms, as well as natural trails and river parks. Prior research conducted in Canada by Campaniaris et al (2015) found difficulties in clustering as a strategic response to global, low cost suppliers. Low levels of open communication and cooperation were not found to fortify small- and medium-sized enterprise (SME) horizonal clustering, and thus, a closer examination of US SMEs is warranted for examining concepts involving social capital and knowledge sharing.…”
Section: Methodsmentioning
confidence: 99%
“…Further questions arise as to why the participants in the annual apparel summit events who were engaged in discussions of a cooperative nature did not develop stronger network ties that progressed to a collaborative stage advancing a cluster economy. Higher levels of open communication and cooperation are suggested, based on earlier work by Campaniaris et al (2015), to be necessary for fortifying SME horizontal clustering. Additionally, further research is needed to examine levels of trust and reciprocity along the supply chain.…”
Section: Limitationsmentioning
confidence: 99%
“…Smaller firms also concentrate on fewer opportunities, relative to larger companies, which again enables their quickness (Burns & Stalker, 1961;Mintzberg, 1979Mintzberg, , 1983Rumelt et al, 1994). As a result of being in close proximity to and knowledge of product customization needs for the local market, SMEs can grow quickly as a niche player (Campaniaris et al, 2015).…”
Section: Niche Strategies In Smesmentioning
confidence: 99%